2018
DOI: 10.7189/jogh.08.010413
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and clinical predictors for Loiasis

Abstract: BackgroundLoiasis is a vector-borne disease in Central and West Africa. While there is still uncertainty to what extent loiasis is responsible for population morbidity, individuals having both loiasis and onchocerciasis have a high risk of fatal encephalopathy when treatment (ie, ivermectin) for onchocerciasis is given. Therefore it is current policy that communities of high loiasis-burden are excluded from mass drug administration programmes of ivermectin. To address this treatment gap we present diagnostic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The majority of clinical data in scientific literature stem from reports on travelers and temporary residents of endemic regions [1,[7][8][9][10][11]. Only few studies systematically evaluated the clinical picture of loiasis in long-term residents of endemic regions, not least due to the supposedly benign disease course [4,[12][13][14][15][16][17]. Chronic infection has been associated with unspecific manifestations, such as itching, body pains or fatigue and importantly, individuals with high microfilarial densities are known to be at risk for spontaneous or treatment-related severe manifestations and excess mortality [1,7,12,13,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of clinical data in scientific literature stem from reports on travelers and temporary residents of endemic regions [1,[7][8][9][10][11]. Only few studies systematically evaluated the clinical picture of loiasis in long-term residents of endemic regions, not least due to the supposedly benign disease course [4,[12][13][14][15][16][17]. Chronic infection has been associated with unspecific manifestations, such as itching, body pains or fatigue and importantly, individuals with high microfilarial densities are known to be at risk for spontaneous or treatment-related severe manifestations and excess mortality [1,7,12,13,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The place of residence of the populations in these studies may partly explain the differences in prevalence observed. Indeed, people who live in endemic areas, mainly in rural settlements, are more exposed to Chrysops (loiasis vector) bites than their counterparts living in urban areas [25,28,29]. In the survey performed by Bouyou-Akotet et al, for example, two-thirds of the population came from rural areas, which could explain the higher prevalence observed in that study [1].…”
Section: Discussionmentioning
confidence: 82%
“…loa microfilaraemia (i.e. > 20,000 microfilariae/milliliter blood) [ 27 ]. To overcome this treatment gap, a so called ‘Test and not treat’ strategy was developed which is based on withholding mass drug administration from those people with high levels of L .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the implementation of ivermectin-based mass drug administration for the control of onchocerciasis or lymphatic filariasis has been impaired because of afore-mentioned serious adverse events in persons with a high L. loa microfilaraemia (i.e. > 20,000 microfilariae/milliliter blood) [27]. To overcome this treatment gap, a so called 'Test and not treat' strategy was developed which is based on withholding mass drug administration from those people with high levels of L. loa microfilariae [28,29].…”
Section: Discussionmentioning
confidence: 99%